Experimental evidence that effects of megaherbivores on mesoherbivore space use are influenced by species' traits. Issue 11 (13th July 2021) - Wells, Harry B. M.; Crego, Ramiro D.; Opedal, Øystein H.; Khasoha, Leo M.; Alston, Jesse M.; Reed, Courtney G.; Weiner, Sarah; Kurukura, Samson; Hassan, Abdikadir A.; Namoni, Mathew; Ekadeli, Jackson; Kimuyu, Duncan M.; et al.
Abstract: The extinction of 80% of megaherbivore (>1, 000 kg) species towards the end of the Pleistocene altered vegetation structure, fire dynamics and nutrient cycling world‐wide. Ecologists have proposed (re)introducing megaherbivores or their ecological analogues to restore lost ecosystem functions and reinforce extant but declining megaherbivore populations. However, the effects of megaherbivores on smaller herbivores are poorly understood. We used long‐term exclusion experiments and multispecies hierarchical models fitted to dung counts to test (a) the effect of megaherbivores (elephant and giraffe) on the occurrence (dung presence) and use intensity (dung pile density) of mesoherbivores (2–1, 000 kg), and (b) the extent to which the responses of each mesoherbivore species was predictable based on their traits (diet and shoulder height) and phylogenetic relatedness. Megaherbivores increased the predicted occurrence and use intensity of zebras but reduced the occurrence and use intensity of several other mesoherbivore species. The negative effect of megaherbivores on mesoherbivore occurrence was stronger for shorter species, regardless of diet or relatedness. Megaherbivores substantially reduced the expected total use intensity (i.e. cumulative dung density of all species) of mesoherbivores, but only minimally reduced the expected species richness (i.e. cumulative predicted occurrence probabilities of all species) of mesoherbivores (by <1 species). Simulated extirpation of megaherbivores altered use intensity by mesoherbivores, which should be considered during (re)introductions of megaherbivores or their ecological proxies. Species' traits (in this case shoulder height) may be more reliable predictors of mesoherbivores' responses to megaherbivores than phylogenetic relatedness, and may be useful for predicting responses of data‐limited species. Abstract : Megaherbivore (re)introductions have been proposed as a means to restore lost ecosystem functions associated with megafaunal extinctions. However, the effects of megaherbivores on smaller herbivores are poorly understood. Long‐term exclosure experiments reveal that megaherbivores generally suppress other herbivores in ways that are influenced by species' traits such as height.